ENT 530 Case Study: Feqa Studio / Abang Iffat Syahmi Abang Djohan ... [et al.] - Abang Djohan, Abang Iffat Syahmi; Abdullah, Afandi Aqmal; Abdul Jamil, Afrina Rauhah; Noordin, Mohd Norakmaal Hakimi; Noor Alamshah, Nur Atirah Zahrah; Allhadi, Nur Nillam Sari; Mohd Rafiz, Sarah Jasmin (2021)
Feqa Studio is a small business founded by Miss Afeqa Dahan in January 2021 as a beginning of a new start. Miss Afeqa adores art and is rather skillful in fashion which is how she was inspired to start the business. Due to the pandemic, cut of budget and lack of transportation, she had to quit her job at Hilman.co and to find other ways to survive. She has been fond of influencing people with her fashion and she turned her account into a gift box service which not only helped her survive the pandemic but also manage to make the business successful and possible for it to be her main income. She made it her mission to spread happiness using her artistic service and to bring a smile to others faces with surprise.